MENINGKATKAN MINAT KUNJUNG ULANG WISATAWAN MELALUI PENERAPAN EXPERIENTAL MARKETING PADA OBJEK WISATA BUATAN DI BANDAR LAMPUNG - Pratisti, Cahyani; Anggraini, Anggraini; Wahyuningsih, Yusminar (Sekolah Tinggi Ilmu Ekonomi Jayakarta, 2024)
ABSTRACT Intention to revisit is an essential indicator for managers of tourist attractions, tourism activists, and tourism offices in a country. As we know, the income from the tourism sector is quite large for Indonesia and continues to grow. One kind of tourist attraction that could be develop is an artificial tourist attraction. One method to attract tourists that are widely developed is experiental marketing. This method was adopted in various provinces in Indonesia such as Bali, Bandung, and Yogyakarta, but unfortunately not yet in Lampung. This survey of 150 tourists used purposive sampling aims to see the effect of experiential marketing which included sense, feel, think, act, and related to the tourists' revisit intention in Lembah Hijau. Multiple regression and descriptive analysis showed that only thinking and relate affected tourists' revisit intentions. We found that with only a little research on experiential marketing in Indonesia, especially in Lampung Province, further development in terms of methods, analytical tools, and breadth of objects and subjects is widely open for the development of experiental marketing in the tourism sector of Indonesia and Lampung province of course. Keywords: Re-visit Intention, Experiental Marketing, Artificial Tourist Attraction, Tourism.